(untitled) (The International Journal for Scientific Research, 2026)
This research examines the legal effects of a valid contract between parties under the Saudi Civil Transactions Law, alongside recent judicial applications. Employing a descriptive-analytical and applied methodology, the study analyzes statutory provisions and relevant Saudi court rulings. It concludes that a valid contract requires the fulfillment of essential pillars: sound mutual consent, a lawful and possible object, a legitimate cause, contractual capacity, and freedom from vitiating factors. Upon formation, the contract immediately creates binding reciprocal obligations, with specific performance serving as the primary mode of execution, all governed by the principles of good faith, custom, and the contract’s nature. The research further demonstrates that breach of contractual obligations triggers a comprehensive remedial framework, including specific performance, judicial rescission, damages, the defense of non-performance, and automatic termination due to impossibility. The courts retain discretionary authority to restore contractual equilibrium in cases of supervening hardship, abusive adhesion clauses, or abuse of rights. The study highlights the Civil Transactions Law’s pivotal role in enhancing legal certainty and contractual stability in Saudi Arabia, concluding with practical recommendations emphasizing precise contract drafting, institutionalizing good faith, publishing guiding judicial principles, promoting alternative dispute resolution, and integrating case law into legal curricula to bridge theoretical instruction with practical application.